Development of fish cupula inspired multi-fluidic sensor for liquid slosh detection - Ahmad, Mohd Ashraf; Musa, Zulkifli; Zawawi, Mohd Anwar; Mohd Falfazli, Mat Jusof; Mohd Rashid, Muhammad Ikram; Suid, Mohd Helmi; Zaharuddin, Mohamed
Liquid slosh in a moving vehicle tank will be hazardous to road users and drivers. Because of sloshing liquid in the tank, it is producing some momentum shift in a moving tank truck. Due to these phenomena the tanker truck will be in imbalance position and cause uncontrolled truck. Therefore, to decrease the number of accidents involving lorry carrying liquid, a liquid sloshing sensor is developed to carefully detect the slosh of the liquid and provide an accurate data to control the liquid slosh. Therefore, the objective of this project is to create a slosh detector that mimics the fish cupula structure is considered to observe the liquid slosh behaviour. Using the accelerometer as a detector device, the wave height reading generated by tank movement can be identified and analyzed. This project uses Arduino UNO as a controller to the entire system, as well as communication between the accelerometer and the LabVIEW. Here, the Arduino can manage the connection between the voltage applied to the remote-control car and the sensor data that capture the slosh generated by the tank's movement. It is clarified that the higher the value of the voltage applied to the remote-control car, the higher the reading of the slosh captured by the accelerometer. In addition, the analysis of the sensor reading with respect to the volume of water in the tank is also shown to identify the suitable volume of water in the tank. Based on the above analysis, in order to produce optimum liquid slosh sensor reading, the suitable input voltage of 5 volt for 4 seconds for ¾ volume of water in the tank. On the other hand, this study also develops the dynamic model of the liquid slosh based on the liquid slosh data from the proposed sensor. Here, the identification of liquid slosh using the Hammerstein model based on Sine Cosine Algorithm (SCA). In contrast to other research works, a piece-wise affine function is considered in a nonlinear function of the Hammerstein model, which is more generalized function. Moreover, a continuous-time transfer function is utilized in the Hammerstein model, which is more suitable to represent a real system. The SCA method is used to tune both coefficients in the nonlinear function and the transfer function of the Hammerstein model such that the error between the identified output and the real experimental output is minimized. The effectiveness of the proposed framework is assessed in terms of the convergence curve response, output response, and the stability of the identified model through the pole-zero map. The results show that the SCA based method can produce a Hammerstein model that yields identified output response closes to the real experimental slosh output with 80.44 % improvement of sum of quadratic error.